Novel and legacy poly- and perfluoroalkyl substances (PFASs) in indoor dust from urban, industrial, and e-waste dismantling areas: The emergence of PFAS alternatives in China. (August 2020) - Zhang, Bo; He, Yuan; Huang, Yingyan; Hong, Danhong; Yao, Yiming; Wang, Lei; Sun, Wenwen; Yang, Baoqin; Huang, Xiongfei; Song, Shiming; Bai, Xueyuan; Guo, Yuankai; et al.
Abstract: With the phase out of perfluorooctanesulfonate (PFOS) and perfluorooctanoic acid (PFOA), the composition profiles of poly- and perfluoroalkyl substance (PFAS) in our living environment are unclear. In this study, 25 PFASs were analyzed in indoor dust samples collected from urban, industrial, and e-waste dismantling areas in China. PFOS alternatives, including 6:2 chlorinated polyfluorinated ether sulfonate (6:2 Cl-PFESA) (median: 5.52 ng/g) and 8:2 chlorinated polyfluorinated ether sulfonate (8:2 Cl-PFESA) (1.81 ng/g), were frequently detected. By contrast, PFOA alternatives, such as hexafluoropropylene oxide dimer acid (HPFO-DA, Gen-X) and ammonium 4, 8-dioxa-3H-perfluorononanoate (ADONA), were not found in any of the dust samples. As expected, all legacy PFASs were widely observed in indoor dust, and 4 PFAS precursors were also detected. Dust concentrations of 6:2 Cl-PFESA were strongly correlated ( p  < 0.05) with those of 8:2 Cl-PFESA regardless of sampling sites. 6:2 Cl-PFESA was also significantly associated with that of PFOS in industrial and e-waste ( p  < 0.01) areas. Association analysis suggested that the sources of PFOS and its alternatives are common or related. Although ∑Cl-PFESA concentration was lower than that of PFOS (17.4 ng/g), industrial areas had the highest 6:2 Cl-PFESA/PFOS ratio (0.63). Composition profiles of PFASs in the industrial area showed the forefront of fluorine change. Thus, the present findings suggested that Cl-PFESAs are widely used as PFOS alternatives in China, and high levels of human Cl-PFESA exposure are expected in the future. Short-chain PFASs (C4–C7) were the predominant PFASs found in dust samples, contributing to over 40% of ∑total PFASs. Furthermore, perfluoro-1-butanesulfonate/PFOS and perfluoro- n -butanoic acid (PFBA)/PFOA ratios were 2.8 and 0.72, respectively. These findings suggested shifting to the short-chain PFASs in the environment in China. To the authors knowledge this is the first study to document the levels of 6:2 Cl-PFESA, 8:2 Cl-PFESA in indoor dust. Graphical abstract: Image 1 Highlights: The first study to document the levels of 6:2 Cl-PFESA and 8:2 Cl-PFESA in indoor dust. PFOS alternatives, F-53B were frequently detected in all dust samples. Significantly positive associations among 6:2 Cl-PFESA, 8:2 Cl-PFESA and PFOS were found, regardless of sampling sites. High composition profiles of short-chain PFASs (C4-C7) indicated an ongoing shift to short-chain alternatives in China. Abstract : This study indicated the wide application of PFOA and PFOS alternatives in China and the shifting of PFAS profiles in the indoor environment.